THE DEVELOPMENT OF ECONOMIC STRUCTURE AND INTER-INDUSTRY LINKAGES IN THE BALTIC COUNTRIES - Šidlauskaitė, Brigita; Miškinis, Algirdas (Ekonomika, 2013)
Abstract. The article presents an analysis of the production and trade structure in three Baltic countries. Both exports and imports were emphasized, pointing out the importance of regional shifts and specialization patterns. The research was performed using the input–output model to determine the relative importance of respective production changes over time and the key differences among the Baltic countries. The paper also analyses the backward and forward inter-industry linkages of manufacturing and service industries. The results have indicated that during the period under analysis the share of sectors creating a lower value added has decreased, and a deeper economic integration was observed in the majority of industrial sectors of the Baltic countries with manifesting stronger forward linkages. Key words: inter-industry linkages, economic structure, the Baltic countries